Evaluation of the rheological properties of stirred yogurt thickened with modified cassava (Manihot esculenta, Crantz) and taro (Colocasia sp.) starch (Research, Society and Development, 2024)
This study aimed to assess the impact of modified cassava (Manihot esculenta Crantz) and taro (Colocasia sp.) starches on the rheological properties of homemade yogurt. Five treatments were tested: yogurt thickened with 0.5% (AM 0.5%) and 1% (AM 1%) cassava starch, yogurt thickened with 0.5% (AI 0.5%) and 1% (AI 1%) taro starch, and a control (yogurt without any thickener). The starches were subjected to physical modification and were incorporated into the yogurt, and then evaluated for rheological properties, apparent viscosity, texture, water retention capacity and syneresis. The result showed that the apparent viscosity was higher in yogurts produced with starches at all analysis speeds, however, the control treatment only showed significant differences with AM 0.5% and AI 0.5% (p